The Story of Surnames and Geneaology - Bowman, William D. (London George Routledge & Sons, 1932)
Originally published London 1932, this fascinating book takes an in-depth look at surnames and geneology, and will prove a fantastic reference book to anyone studying the subjects. Contents include: Local Names; Address Surnames; Patronymics; Prophets, Martyrs, Warriors; Matronymics; Names from Miracle Plays; Fourteenth Century London; Nicknames; Names from Pastimes; Nicknames from Dispositions; Foreign Names; Craftsmen and Officials; Teutonic Surnames; American Surnames; Index of Surnames. Many of the earliest books, particularly those dating back to the 1900s and before, are now extremely scarce and increasingly expensive. We are republishing these classic works in affordable, high quality, modern editions, using the original text and artwork.
Keywords: Geneaology; Surnames; Names, Personal -- England -- United States